Peningkatan Produktivitas UMKM Melalui Pelatihan Dan Strategi Pengembangan Produk Lokal Di Dukuh Kalangan - Ihsan, Farhan Taufiqul; Atmaja, Ragil Nugroho Danu; Mayesti, Reza Tri; Agustina, Putri; Sari, Risa Hentika; Nurlailayah, Prima Diaz Eka; Prasetyo, Edy; Amaludin, Ilham; Alqarnist, Abdul Waiz; Suryani, Lilis (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
The main issue faced by MSMEs in Kalangan Hamlet, Kebon Agung, Imogiri, is the limited knowledge of digital marketing and the lack of innovation in product design. This hinders their competitiveness in the market. The program on digital marketing and product design for MSME actors in Kalangan Hamlet was conducted as an effort to enhance entrepreneurs' understanding and skills in developing more effective and innovative marketing strategies. The goal of this Community Service program is to provide insights into the importance of digital marketing, utilizing social media, and applying attractive product designs to increase sales value. The method used in this program is socialization, which includes delivering materials, interactive discussions, and providing examples of marketing strategies and product designs that align with market trends. The training participants are residents of Kalangan Hamlet who have home-based industries. The socialization and training took place on February 8, 2025, at the Kendalisada Arts Center, Kalangan. The instructors were faculty members and students from UMY. The results of the socialization and training showed that participants gained a better understanding of how to utilize social media as a marketing tool, create engaging content strategies, and the importance of product design that aligns with brand identity. Most participants recognized the need to adapt to technological advancements and began considering the implementation of digital strategies in their businesses. However, challenges arose in direct implementation, particularly the limited access to technology and the readiness of resources. Therefore, follow-up actions such as mentorship or the formation of an MSME community are necessary to ensure the sustainability of the strategies that have been socialized. With this program, it is expected that MSMEs in Kalangan Hamlet will be better prepared to face increasingly competitive market challenges and enhance the sustainable growth of their businesses